Effect of Pre-gelatinized Wheat Starch on Physical and Rheological Properties of Shortened Cake Batter and Cake Texture - Ebrahimi, F.; Tarzi, B. G.; Asghari, M. (Engineering, Technology & Applied Science Research, 2016)
The focus of this study was the effect of 1.5%, 3% and 4.5% pre-gelatinized wheat starch (based on the total weight of cake batter) on improving the qualitative properties of shortened cake batter. Specific volume and viscosity of the shortened cake batter were measured for controls, 1.5%, 3% and 4.5% gelatinized starch; some important properties such as texture and sensory evaluation were examined. By increasing pre-gelatinized wheat starch used in the batter, a significant difference was observed in the rheological properties of the batter. Cake batter properties were found improved compared to the control samples. The sample with 3% pre-gelatinized starch had a lower viscosity than other treatments. The treatment with 4.5% pre-gelatinized starch had the lowest specific volume compared to other treatments. The overall results showed that the shortened cake with 3% pre-gelatinized starch was the best treatment in terms of texture and sensory evaluation factors.